2021
DOI: 10.3390/w13223224
|View full text |Cite
|
Sign up to set email alerts
|

Solvothermal Synthesis of ZnO Nanoparticles for Photocatalytic Degradation of Methyl Orange and p-Nitrophenol

Abstract: The photocatalytic degradation of organic pollutants is an effective method of controlling environmental pollution. ZnO nanoparticles (ZnO NPs) were prepared by the solvothermal method and characterized by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and UV–visible diffuse reflectance spectroscopy (UV–Vis DRS). The results showed that the ZnO NPs had a uniform size of 25–40 nm, hexagonal wurtzite structure, and a band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 46 publications
2
8
0
1
Order By: Relevance
“…The theoretical value for the band-gap energy is 3.37 eV and is higher than the calculated band-gap energy values for all three samples. Nevertheless, they are in concordance with other literature reports [ 41 , 42 ]. The existence of crystalline defects on the nanoparticle surface, as determined by the XRD data, creates inside the band-gap additional electronic levels, which in turn leads to smaller energy values [ 43 ].…”
Section: Resultssupporting
confidence: 93%
“…The theoretical value for the band-gap energy is 3.37 eV and is higher than the calculated band-gap energy values for all three samples. Nevertheless, they are in concordance with other literature reports [ 41 , 42 ]. The existence of crystalline defects on the nanoparticle surface, as determined by the XRD data, creates inside the band-gap additional electronic levels, which in turn leads to smaller energy values [ 43 ].…”
Section: Resultssupporting
confidence: 93%
“…Through the estimation of the valence band maximum (VBM) and the energy band gap (E g ) from XPS and UV-vis spectroscopy; it was possible to build a schematic band edge representation of the two ZnO compounds, figure 9. It is observed that vacancies in the black ZnO structure causes a modification of the band edges moving into a region within a more oxidative character, proposing to black ZnO as a reasonable promotor of OH radicals [14,18]; and thus, opening their exploration as a feasible photocatalyst in the UV visible region; in good concordance with preceding reports where vacancies in the structure of the compounds promotes their catalytic performance [74][75][76][77][78][79].…”
Section: Resultssupporting
confidence: 87%
“…Zinc oxide nanoparticles (NPs) have been synthesized through soft chemical and physical pathways; chemical routes include techniques such as precipitation, sol-gel, hydrothermal, solvothermal and microemulsion [7][8][9][10][11][12][13][14][15] while physical methods comprise ball milling, laser ablation, continuous arc discharge under controlled atmosphere [16][17][18]. Irrespective of which of these two methods is used, ZnO NPs exhibit a reasonable performance as photocatalyst [14,18,19] or as antibacterial activity material [12,13,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…we can determine the direct band-gap energy values by graphical extrapolation to [F(R)•hν] 2 = 0 (Figure 7b). The determined band-gap energy values are smaller than the theoretical value of 3.37 eV, but still close to it [21,34,98]. The multiple surface defects of the nanoparticles, as indicated by the XRD study, induce additional electronic levels inside the band-gap, leading to decreased energy values.…”
Section: Uv-vis Spectroscopymentioning
confidence: 49%